Strategy Of Darul Huda Mayak Islamic Boarding School In Facing Modern and Postmodern Challenges - Mahmudin, Afif Syaiful (MA'ALIM: Jurnal Pendidikan Islam, 2024)
Islamic thought experiences varied dynamics, ups and downs. The clash with Western civilization, which has dominated world civilization, has caused Muslims to rethink their understanding of their religion. Conservative, traditionalist styles of thinking began to be abandoned in the Postmodern era. The tendency to criticize the establishment, modernism and traditionalism is increasingly becoming symptomatic nowadays. To find out about an Islamic boarding school-based educational institution, it is necessary to know the direction of Islamic thought in the Postmodernism era so that we can also know the direction of the Islamic movement in facing this era, especially at the Darul Huda Mayak Ponorogo Islamic Boarding School . The method used in this research is descriptive qualitative. The results of the analysis state that this Islamic boarding school is based on a classical system and is always innovative following the challenges of current developments, with the motto " Ala Nahjis Salafiyatil Haditsah" Pondok Darul Huda will be ready to compete in the field of educational advancement while still maintaining classical values which have proven to be strong any time and circumstances.